The Influence of Dividend Yield on Sales Volume of Sharia Constituent Shares Jakarta Islamic Index 70 - Yulian Ade Chandra; Muhammad Rijalus Sholihin (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
Stock trading is something that is observed and occupied by stock investors, especially retail investors. The large trading volume indicates that the stock is in great demand by investors. Information about stock trading volume is a signal that investors will consider in making decisions. Shareholders can decide to invest by looking at the dividend yield. Investors trying to invest funds with stocks that have high dividend yields. The purpose of this study is to determine whether the dividend yield variable has a significant effect on the stock trading volume of the constituents of the Jakarta Islamic Index 70. This research method uses descriptive quantitative method with secondary data collection in documentation. The results of this study indicate that the dividend yield has no significant effect on the trading volume of the constituent shares of JII 70. These results indicate that there are other variables that should be suspected to be influenced by other variables, especially the company's fundamental variables. Some improvements in data collection criteria also seem to need to be done for further research in order to obtain optimal results.